2019
DOI: 10.1111/spol.12529
|View full text |Cite
|
Sign up to set email alerts
|

The Troubled Families Programme: Learning about policy impact through realist case study research

Abstract: This article aims to critically explore how qualitative case study research that is founded on realist principles can fundamentally enhance social policy evaluation methodologies and, in turn, provide improved learning for policy makers and practitioners. We suggest these methodological advantages are accrued through the careful construction of theory-based explanations of 'how' policy programmes work thereby addressing the limitations of quasi-experimental methods -namely a focus on and prioritisation of outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…The agency also uses its own evidence hierarchy to judge the quality of current studies, where RCTs are considered the best evidence available, followed by multivariate analyses with controls for observed differences and effect evaluations based on individual panel data. Similar is found in the UK, where randomized control trials are regarded as the gold standard in several official evaluations in the field of social policy (Parr & Churchill, 2019).…”
Section: Methodological Idealssupporting
confidence: 58%
“…The agency also uses its own evidence hierarchy to judge the quality of current studies, where RCTs are considered the best evidence available, followed by multivariate analyses with controls for observed differences and effect evaluations based on individual panel data. Similar is found in the UK, where randomized control trials are regarded as the gold standard in several official evaluations in the field of social policy (Parr & Churchill, 2019).…”
Section: Methodological Idealssupporting
confidence: 58%
“…The government claimed that the intervention, which initially targeted social support for 120,000 families living on low incomes and with complex problems, had a 100% success rate (DCLG, 2015). However, the independent evaluation suggested that the impact in terms of increasing employment, improving health outcomes, and reducing antisocial behaviour was limited and questioned the robustness of the evaluation design and the data collected (Day et al, 2016; Parr & Churchill, 2019). It is also notable that one of the key factors identified in the collapse of the high‐profile United Kingdom children's charity Kids Company , which aimed to help children living in poverty, was a lack of robust internal or independent evaluation evidence to assess the impact and cost effectiveness of the outcomes of education and employment interventions (House of Commons, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the short term, they are likely to require additional resources, and assessing cost-effectiveness can only take place over time because savings occur with reduced duplication of services and reduced dependence on services longterm. Recognizing a full range of potential outcomes, including 'soft' outcomes such as increases in families' subjective experience of wellbeing and increased engagement with services, has been highlighted (Batty, 2014;Parr & Churchill, 2019). A more nuanced outcome framework, distinguishing between transformative change, stabilizing, and crisis management, to allow for the recognition of significant results that fall short of transformative change is recommended (Batty & Flint, 2012).…”
Section: Challengesmentioning
confidence: 99%